Studi Literatur: Kemampuan Pembuktian Matematis Mahasiswa Pada Pembelajaran Matematika - Hajar Marhani; Rusi Ulfa Hasanah; M. Fahrozi Tanjung (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
The purpose of this research is to find out about students' mathematical abilities and proofs when learning mathematics at the tertiary level. In this research, researchers used quantitative methods in the form of literature reviews or literature reviews, namely this research took data sources from books, journals and previous research that had been carried out. Apart from that, it is also based on the results of the researcher's analysis, where this theoretical reference can be used as a strong basis for understanding students' mathematical proof abilities. Based on the research results obtained by researchers, it is that students' mathematical proof abilities are not optimal, and based on the research results, the percentage of mathematical proof abilities obtained is less than optimal. The majority of students still have difficulty working on proof questions. This is due to various factors, one of which is that understanding of integers and their definitions and properties is still low.